La motivación en el rendimiento académico de los y las estudiantes de segundo año de Educación Básica de la escuela Isidro Ayora - Gamboy Soria, María Gabriela (2021)
The present research work with the title: Motivation in the academic performance of the students of the second year of basic education of the Isidro Ayora School; It is generated due to the need to give a supportive response to the problem that revolves around determining how motivation affects the academic performance of students; For this purpose, the general objective has been to strengthen academic performance through motivation; Regarding the work methodology, it has been developed through the Quantitative approach; the research modality is applied, the process support method has been deductive and the data collection technique is the survey with its instrument the questionnaire; after which it has been possible to conclude that; Among the main results of the applied survey, it has allowed to verify the existence of many difficulties in the implementation of constant motivation in the classroom, due to the ignorance of strategies that are valid and applicable in the reality of the educational institution. Among the main results of the application of the proposal, it is evident that 100% of the indicators are achieved at the Excellent level; In general, the result of the research process shows that an important strengthening of the Academic Performance has been achieved through the Motivation of the students in all the subjects of the curriculum that corresponds to them.